2007
DOI: 10.1073/pnas.0705407104
|View full text |Cite
|
Sign up to set email alerts
|

PAS kinase is required for normal cellular energy balance

Abstract: The metabolic syndrome, a complex set of phenotypes typically associated with obesity and diabetes, is an increasing threat to global public health. Fundamentally, the metabolic syndrome is caused by a failure to properly sense and respond to cellular metabolic cues. We studied the role of the cellular metabolic sensor PAS kinase (PASK) in the pathogenesis of metabolic disease by using PASK ؊/؊ mice. We identified tissue-specific metabolic phenotypes caused by PASK deletion consistent with its role as a metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
157
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(179 citation statements)
references
References 51 publications
14
157
8
Order By: Relevance
“…Therefore, all the observed changes suggest that a decrease in both mitochondrial oxidative activity and mitochondrial adenosin triphosphate (ATP) synthesis could underlie the susceptibility to HFD-induced obesity. This hypothesis is in agreement with the results obtained by Hao et al (12), which showed that mice with deleted PAS kinase (a cellular metabolic sensor) are resistant to high fat diet-induced obesity and insulin resistance, partly due to an increase in the rate of oxidative metabolism and ATP production. This finding could explain why after a high fat load of 50% of their energy requirements, obese-susceptible subjects were not able to increase their rates of fat oxidation more than the lean subjects, despite their higher metabolic mass (25).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, all the observed changes suggest that a decrease in both mitochondrial oxidative activity and mitochondrial adenosin triphosphate (ATP) synthesis could underlie the susceptibility to HFD-induced obesity. This hypothesis is in agreement with the results obtained by Hao et al (12), which showed that mice with deleted PAS kinase (a cellular metabolic sensor) are resistant to high fat diet-induced obesity and insulin resistance, partly due to an increase in the rate of oxidative metabolism and ATP production. This finding could explain why after a high fat load of 50% of their energy requirements, obese-susceptible subjects were not able to increase their rates of fat oxidation more than the lean subjects, despite their higher metabolic mass (25).…”
Section: Discussionsupporting
confidence: 93%
“…However, an analysis of pancreatic beta cells from mice in which the kinase domain has been removed (PASK knockout) showed that Pask mRNA expression did not respond to elevated glucose concentrations, and no differences in glucose-stimulated insulin production were found between both types of mice [31]. Later studies indicated that PASK-deficient mice are resistant to diet-induced obesity, with this effect being related to an increase in the metabolic rate in skeletal muscle, although there was no effect on the function of other metabolic sensors (AMPK, mTOR) [7].…”
Section: Discussionmentioning
confidence: 99%
“…PASK Expression Responds to Fasting and Re-feeding in VMH and LH from Wild-Type Mice PASK has already been proposed as a nutrient sensor [7], so we analysed PASK mRNA expression under fasting and refeeding conditions in VMH and LH from wild-type and PASK-deficient mice. In order to ensure the purity of these hypothalamic nuclei obtained by micropunching from mouse hypothalamus, Sf-1 and prepro-orexin genes were used as markers of these specific nuclei, respectively.…”
Section: Effect Of Pask Deficiency On the Expression Of Metabolic Genmentioning
confidence: 99%
See 1 more Smart Citation
“…The da Silva Xavier study focuses on the per-arnt-sim (PAS) domain kinase (PASK), another serine/threonine kinase [18] implicated in the sensing of cellular energy homeostasis, the control of insulin gene expression [19] and the modulation of insulin gene expression under pathophysiological cell culture conditions [20]. However, while Pask -/-mice displayed reduced plasma insulin responses to glucose they showed normal glucose [21,22] and insulin [21] tolerance. da Silva Xavier et al now examine whether PASK may function as a metabolic sensor in alpha cells.…”
mentioning
confidence: 99%